Gendering welfare state analysis: tensions between care and paid work - Ciccia, R; Sainsbury, D (Bristol University Press, 2018)
The article revisits comparative research on gender relations and the welfare state through the lens of the tensions between paid work and care. It discusses how these tensions shaped the intellectual enterprise of gendering welfare state analysis and women's political activity in the welfare state, as well as the emergence of normative perspectives to overcome divisions between care and paid work. It concludes by identifying three challenges for future research posed by intersectionality, immigration and the gender implications of long-term welfare state change. Nonetheless, the greatest cross-cutting challenge remains the need to balance care and paid work in feminist analysis of welfare states.